Modeling and Optimization of Heat Recovery Heat Exchanger - Kaviri, Ganjeh; Tholudin, M.L.; Mohd Jafar, M.N. (Applied Mechanics and Materials, 2012)
The Combined Cycle Power Plants (CCPPs) are attractive in power generation field due to their higher thermal efficiency than individual steam or gas turbine cycles. Therefore thermo optimal design of Heat Recovery Steam Generator (HRSG) in CCPPs is an important subject due to the increasing the fuel prices and decreasing the fossil fuel resources. In this paper the heat recovery steam generator (HRSG) with typical geometry and number of pressure levels used at CCPPs in Iran is modeled. Then the optimal design of HRSG operating parameters was performed by defining an objective function and applying Generic algorithm optimization method. The total cost per unit of produced steam exergy was defined as the objective function. The objective function included capital or investment cost, operational cost, and the corresponding cost of the exergy destruction was minimized while satisfying a group of constraints.